Characterization of TGF-β by Induced Oxidative Stress in Human Trabecular Meshwork Cells - Hsin-Yi Chen; Hsiu-Chuan Chou; Yi-Jung Ho; Shing-Jyh Chang; En-Chi Liao; Yu-Shan Wei; Meng-Wei Lin; Yi-Shiuan Wang; Yu-An Chien; Xin-Ru Yu; Hsiang-Yu Kung; Chu-Chun Yang; et al. (MDPI AG, 2021)
Oxidative stress generated by reactive oxygen species (ROS) plays a critical role in the pathomechanism of glaucoma, which is a multifactorial blinding disease that may cause irreversible damage within human trabecular meshwork cells (HTMCs). It is known that the transforming growth factor-β (TGF-β) signaling pathway is an important component of oxidative stress-induced damage related to extracellular matrix (ECM) fibrosis and activates cell antioxidative mechanisms. To elucidate the dual potential roles and regulatory mechanisms of TGF-β in effects on HTMCs, we established an in vitro oxidative model using hydrogen peroxide (H2O2) and further focused on TGF-β-related oxidative stress pathways and the related signal transduction. Via a series of cell functional qualitative analyses to detect related protein level alterations and cell fibrosis status, we illustrated the role of TGF-β1 and TGF-β2 in oxidative stress-induced injury by shTGF-β1 and shTGF-β2 knockdown or added recombinant human TGF-β1 protein (rhTGF-β1). The results of protein level showed that p38 MAPK, TGF-β, and its related SMAD family were activated after H2O2 stimulation. Cell functional assays showed that HTMCs with H2O2 exposure duration had a more irregular actin architecture compared to normal TM cells. Data with rhTGF-β1 (1 ng/mL) pretreatment reduced the cell apoptosis rate and amount of reactive oxygen species (ROS), while it also enhanced survival. Furthermore, TGF-β1 and TGF-β2 in terms of antioxidant signaling were related to the activation of collagen I and laminin, which are fibrosis-response proteins. Succinctly, our study demonstrated that low concentrations of TGF-β1 (1 ng/mL) preserves HTMCs from free radical-mediated injury by p-p38 MAPK level and p-AKT signaling balance, presenting a signaling transduction mechanism of TGF-β1 in HTMC oxidative stress-related therapies.